Response of corn to depth of water table in lowland soil - Coelho, Eugênio Ferreira; Pereira, Paulo Magela; Caixeta, Tarcisio José; Viana, Maria Celuta Machado; Maia, Aline de Holanda Nunes (Pesquisa Agropecuaria Brasileira, 1992)
The objective of this study was to obtain a suitable water table management strategy for corn (Zea Mays L.) subirrigation in lowland clayey soils. A drainage-subirrigation system was installed with five water table depths: 0.35 m; 0.50 m, 0.65 m; 0.80 m and 0.95 m. Two corn cultivars were grown each one distributed in ten plots for each water table depth. Soil water content, air space measurements, plant height and leaf area data were obtained periodically. After harvesting, the weight of commercial and non-commercial corncobs were measured. The best estimated yields for AG 162 and BR 106 cultivars occurred for 0,53 m and 0,60 m water table depths.
Keywords: drainage; subirrigation; Zea mays